Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1053/j.gastro.2021.04.064
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling in Liver, Pancreas, and Gastrointestinal Diseases and Cancer

Abstract: Genetic alterations affecting transforming growth factor-b (TGF-b) signaling are exceptionally common in diseases and cancers of the gastrointestinal system. As a regulator of tissue renewal, TGF-b signaling and the downstream SMAD-dependent transcriptional events play complex roles in the transition from a noncancerous disease state to cancer in the gastrointestinal tract, liver, and pancreas. Furthermore, this pathway also regulates the stromal cells and the immune system, which may contribute to evasion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 271 publications
0
91
0
1
Order By: Relevance
“…We assigned TGF-β receptor-associated protein 1 (TRAP1), LRG, ubiquitin C-terminal hydrolase 19 (UCH19) and phosphofurin acidic cluster sorting protein 1 (PACS1) to TGF-β signal transduction, which is essential to maintain the homeostasis and normal immune function of the liver, pancreas and gastrointestinal system ( 30 ). The compound formed by TGF-β receptor I (TβR I, also known as activin receptor-like kinase, ALK) and TGF-β receptor II (TβR II) recognizes TGF-β and then phosphorylates the C-termini of the transcription factors Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…We assigned TGF-β receptor-associated protein 1 (TRAP1), LRG, ubiquitin C-terminal hydrolase 19 (UCH19) and phosphofurin acidic cluster sorting protein 1 (PACS1) to TGF-β signal transduction, which is essential to maintain the homeostasis and normal immune function of the liver, pancreas and gastrointestinal system ( 30 ). The compound formed by TGF-β receptor I (TβR I, also known as activin receptor-like kinase, ALK) and TGF-β receptor II (TβR II) recognizes TGF-β and then phosphorylates the C-termini of the transcription factors Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KEGG pathway enrichment analysis suggested that these DE genes were enriched mainly in vascular smooth muscle contraction, focal adhesion, and the TGF beta signaling pathway, and were also closely related to small cell lung cancer, NSCLC, melanoma, glioma, prostate cancer, thyroid cancer, CRC, and other cancers. According to the previous study, the focal adhesion and the TGF beta signaling pathways play essential roles in cell proliferation, and dysregulation of these two pathways is closely associated with oncogenesis [ 27 , 28 ]. In addition, to further verify whether the functional annotations of the DE lncRNAs and mRNAs were basically consistent, we used Venn diagram software to intersect the DE lncRNA target genes and DE mRNAs and found 523 overlapping genes, which were involved mainly in the extracellular matrix, myosin complex, cytoskeleton, and signal transduction, among other processes.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, the focal adhesion and TGF beta signaling pathways play essential roles in cell proliferation, and dysregulation of these two pathways is closely associated with oncogenesis [29,30]. In addition, to further verify whether the functional annotations of the DE lncRNAs and DE mRNAs were basically consistent, we used Venn diagram software to intersect the DE lncRNA target genes and the DE mRNAs and found 523 overlapping genes, which were involved mainly in the extracellular matrix, myosin complex, cytoskeleton, signal transduction, and so on.…”
Section: Discussionmentioning
confidence: 99%